Time-Related Changes in Volatile Compounds during Fermentation of Bulk and Fine-Flavor Cocoa (Theobroma cacao) Beans - Juan Manuel Cevallos-Cevallos; Laura Gysel; Maria Gabriela Maridueña-Zavala; María José Molina-Miranda (Journal of Food Quality)
Chocolate is one of the most consumed foods worldwide and cacao fermentation contributes to the unique sensory characteristics of chocolate products. However, comparative changes in volatiles occurring during fermentation of Criollo, Forastero, and Nacional cacao—three of the most representative cultivars worldwide—have not been reported. Beans of each cultivar were fermented for five days and samples were taken every 24 hours. Volatiles from each sample were adsorbed into a solid phase microextraction fiber and analyzed by gas chromatography-mass spectrometry. Aroma potential of each compound was determined using available databases. Multivariate data analyses showed partial clustering of samples according to cultivars at the start of the fermentation but complete clustering was observed at the end of the fermentation. The Criollo cacao produced floral, fruity, and woody aroma volatiles including linalool, epoxylinalool, benzeneethanol, pentanol acetate, germacrene, α-copaene, aromadendrene, 3,6-heptanedione, butanal, 1-phenyl ethenone, 2-nonanone, and 2-pentanone. Nacional cacao produced fruity, green, and woody aroma volatiles including 2-nonanone, 3-octen-1-ol, 2-octanol acetate, 2-undecanone, valencene, and aromadendrene. The Forastero cacao yielded floral and sweet aroma volatiles such as epoxylinalool, pentanoic acid, benzeneacetaldehyde, and benzaldehyde. This is the first report of volatiles produced during fermentation of Criollo, Forastero, and Nacional cacao from the same origin.